Implementation of the Principle of Publicity in the Charge of Mortgage Guarantees - Lubis, Raihanah Erwina; Harahap, Mhd. Yadi; Alya, T. Damara; Ananda, Aura Balqis (LPPM UIKA Bogor, 2024)
Legal principles are the initial foundation for the formation of a law. In Law no. 4 of 1996 concerning mortgage rights is also based on legal principles that prioritize rights, which of course aims to realize equal rights. Implementation of the Principle of Publicity in Charging Mortgage Guarantees is an important aspect that supports transparency and legal certainty in financial transactions involving collateral objects. The principle of publicity, which requires the registration of mortgage rights to be recognized and enforced against third parties, is the main pillar in the property guarantee system in Indonesia. The question that arises is what is the aim of applying the principle of publicity in the imposition of collateral law. Through normative methods with document analysis and literature study, this writing reveals that even though the principle of publicity has been confirmed in Law no. 4 of 1996 concerning Mortgage Rights over Land and Objects Related to Land, there are still challenges in practice, such as administrative problems and information accessibility. This article concludes that improving the registration system and increasing access to public information is the main key to overcoming these challenges, as well as strengthening the principle of publicity in the imposition of mortgage guarantees in Indonesia. The proposed policy and practice recommendations are expected to help increase legal certainty and efficiency of financial transactions related to property collateral.